The Online Theology Classroom: Strategies for Engaging a Community of Distance Learners in a Hybrid Model of Online Education - Hege, Brent A. R. (Teaching theology and religion, 2011)
One factor contributing to success in online education is the creation of a safe and vibrant virtual community and sustained, lively engagement with that community of learners. In order to create and engage such a community instructors must pay special attention to the relationship between technology and pedagogy, specifically in terms of issues such as course design, social presence, specially tailored assignments, learner expectations, and objectives, and facilitation of sustained engagement with the course material, fellow learners, and the instructor. Several strategies for accomplishing this goal are presented here based on the author's experiences teaching second-career students in hybrid introductory theology courses at a mainline denominational seminary.